Robert S. McNamara at the World Bank : In Retrospect - Lafourcade, Olivier (World Bank, Washington, DC, 2021)
This retrospective on the terms of World Bank President Robert S. McNamara (1968–81) examines his words, actions, and results through the lens of the authors, his six successive personal assistants. They delve into his annual meeting speeches and policy addresses, deconstructing the motivations and actions behind the words. The authors give personal insight into McNamara as president, along with his relations with World Bank staff and world leaders. McNamara’s interactions with a multiplicity of borrowing countries, including China, are highlighted. The sectoral impact of McNamara’s presidency is described in some depth and in relation to current events, including the 1970s’ oil crisis. The conclusion contains a look at the legacy of McNamara, the lasting impact of “McNamara’s Bank,” and a final personal tribute to McNamara.